Back Cover: A New Perspective on Li–SO2 Batteries for Rechargeable Systems (Angew. Chem. Int. Ed. 33/2015). Issue 33 (23rd July 2015) - Lim, Hee‐Dae; Park, Hyeokjun; Kim, Hyungsub; Kim, Jinsoo; Lee, Byungju; Bae, Youngjoon; Gwon, Hyeokjo; Kang, Kisuk
<x xml:space="preserve">Abstract</x> A rechargeable Li–SO2 battery developed from a primary Li–SO2 cell is reported by K. Kang et al. in their Communication on page 9663 ff. Lithium ions (yellow) and sulfur dioxide (blue) reversibly react with each other in the rechargeable system, leading to a high energy density and a superior energy efficiency of the rechargeable Li–SO2 battery. The energy efficiency of the rechargeable system is further enhanced by using catalysts.